Alternative targum traditions : the use of variant readings for the study in origin and history of targum Jonathan - Houtman, Alberdina. (Studies in the Aramaic Interpretation of Scripture, 2009)
The present study explores the possibility of using variant readings of the Targum of the Prophets to get a better insight into the origin and history of Targum Jonathan. The focus is on two sorts of variant readings: the Tosefta Targums and the targumic quotations in rabbinic and medieval Jewish literature. The chapter on the Tosefta Targums concentrates on variants from the book of Samuel. The chapter on the targumic quotations includes quotations of all the Prophets in early Jewish literature. In the Appendix a full list is given of all quotations of Targums of the Prophets presently known. The book is useful for the study of the genesis of Targum Jonathan as well as for its later developments.